A blind watermarking algorithm for fingerprint images based on contourlet transform. (21st November 2014) - Kishore Kumar, N.K.; Sheeba, V.S.
We present a novel blind biometric watermarking algorithm based on contourlet transform in this paper. The host image is decomposed into a series of multiscale, local and directional subimages using contourlet transform. A high frequency directional sub-band which has the highest energy is used for watermarking. At the same time, the original binary watermark is scrambled by two-dimensional Arnold transform, and then embedded into the selected directional sub-band. The signs of the contourlet coefficients are modified depending on the watermark bit. The watermark retrieving algorithm is a blind detection process, and it does not need the original image. Iris code is taken as the watermark and finger print image is taken as the host image. The simulation results show that the proposed watermarking algorithm gives good perceptual transparency and is able to resist additive channel noise attacks, cropping, histogram equalisation, gamma correction, etc.